(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of research on identification of the optimal time for planting uterine bulbs for the seed yield and its quality of onions in the conditions of the south of Uzbekistan. The optimal timing of planting the uterine onion bulbs is recommended.